Role of sirtuin 1 in the brain development in congenital hypothyroidism rats via the regulation of p53 signaling pathway. Issue 4 (1st April 2022) - Wei, Xiaofang; Tan, Juan; Gao, Hui
ABSTRACT: The present study aimed to investigate the expression, role, and underlying mechanism of action of sirtuin 1 (SIRT1) in congenital hypothyroidism (CH). A CH model was established in rats, and neuronal cells were isolated from the hippocampal tissues of normal rats. Free thyroxine (fT4) and thyroid-Stimulating hormone (TSH) concentrations were determined to confirm CH model conduction. The cognitive behavior of rats with CH was examined using open field and forced swimming tests. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting were used to detect the expression levels of SIRT1, p53, B-cell lymphoma-extra-large (Bcl-xl), Bcl-2-associated X (Bax), and cytochrome c in the hippocampal tissues and neuronal cells. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide assay and flow cytometry were performed to evaluate cell viability and apoptosis, respectively. The results revealed that SIRT1 was expressed at low levels in the hippocampal tissues of rats with CH. Moreover, overexpression of SIRT1 in the hippocampal tissues of rats with CH and improved rat behavior, while reducing the CH-induced nerve cell apoptosis. In addition, this overexpression increased the viability, inhibited apoptosis, and reduced the expression of p53, Bax, and cytochrome c, while increasing the expression of Bcl-xl in cultured neurons. In contrast, SIRT1-small interfering RNA exhibited the opposite effects in cultured neurons. In conclusion, SIRT1 plays a role in the occurrence and development of CH by regulating nerve cell apoptosis. Graphical abstract: uf0001